Penegakan Hukum Terhadap Penyalahgunaan Tanda Nomor Kendaraan Roda Dua Dalam Kasus Tilang Elektronik - Muhammad Bagas Handono; Ahmad Sudiro (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The enforcement of legal measures against the misuse of registration plates on two-wheeled vehicles has become a critical concern in Indonesia's traffic system. This issue is exacerbated by the increasing number of violations leading to erroneous electronic fines (e-tickets), undermining public trust in the legal system. According to 2023 data from the Indonesian National Police, over 500 cases of counterfeit license plate usage resulted in misdirected e-tickets. This study examines the enforcement of laws addressing the misuse of vehicle registration plates under Law No. 22 of 2009 on Road Traffic and Transportation. It focuses on identifying weaknesses in the current legal framework and ensuring the application of justice in cases of misallocated fines. Employing a normative juridical approach, this research analyzes existing regulations and evaluates relevant cases. The findings indicate that such misuse contravenes Articles 280 and 288 of Law No. 22 of 2009, which stipulate compliance with technical specifications and legality in vehicle registration. However, enforcement efforts face challenges such as inadequate monitoring tools and the lack of integrated vehicle data systems. This study recommends enhancing the data verification processes in e-ticketing systems and fostering stronger collaboration between law enforcement and related agencies to address these issues. Such measures aim to improve legal accountability and ensure equitable traffic supervision. By tackling these systemic shortcomings, the research contributes to restoring public confidence in traffic law enforcement and promoting a more effective legal framework for road safety in Indonesia.